2022
DOI: 10.3389/fphys.2022.1012887
|View full text |Cite
|
Sign up to set email alerts
|

Serum high-sensitive C-reactive protein is a simple indicator for all-cause among individuals with MAFLD

Abstract: High-sensitive C-reactive protein (hs-CRP) is one of the diagnostic components for metabolic (-dysfunction) associated fatty liver disease (MAFLD). This study aimed to explore the relationship between hs-CRP level and 25-year mortality in patients with MAFLD. The study data were from the Third National Health and Nutrition Examination Survey 1988–1994. All participants were followed up until December 2015 and the outcome of each participant was ascertained from National Death Index records. Cox proportional ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
0
6
0
Order By: Relevance
“…Some early dampened CRP responses post-liver resection can reflect a poor hepatic reserve that could have prognostic value [ 340 ]. Importantly, a study demonstrated that increased hsCRP titers were linked to an increased risk of Metabolic-dysfunction Associated Fatty Liver Disease (MAFLD) in obese individuals, and it was also positively associated with the severity of liver steatosis and fibrosis; therefore, it may be used as a possible biomarker to monitor and estimate disease severity, while another study concluded that hsCRP can be an independent predictor of poor prognosis—even fatal outcomes—in MAFLD patients [ 341 , 342 ]. Interestingly, a study on rats showed that increased CRP levels can be an early sign of Alcoholic Fatty Liver (AFL), whereas another study concluded that CRP seems to be an accurate marker of alcoholic hepatitis [ 343 , 344 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…Some early dampened CRP responses post-liver resection can reflect a poor hepatic reserve that could have prognostic value [ 340 ]. Importantly, a study demonstrated that increased hsCRP titers were linked to an increased risk of Metabolic-dysfunction Associated Fatty Liver Disease (MAFLD) in obese individuals, and it was also positively associated with the severity of liver steatosis and fibrosis; therefore, it may be used as a possible biomarker to monitor and estimate disease severity, while another study concluded that hsCRP can be an independent predictor of poor prognosis—even fatal outcomes—in MAFLD patients [ 341 , 342 ]. Interestingly, a study on rats showed that increased CRP levels can be an early sign of Alcoholic Fatty Liver (AFL), whereas another study concluded that CRP seems to be an accurate marker of alcoholic hepatitis [ 343 , 344 ].…”
Section: Current Evidence On C-reactive Protein and Potential Conditionsmentioning
confidence: 99%
“…According to the findings of a Cox regression analysis, hs-CRP levels below 0.5 mg/dL are an independent risk factor for mortality from all causes, cardiovascular disease, and malignancy. Hs-CRP could successfully differentiate MAFLD with poor prognosis and mortality risk at a level of 0.5 mg/dL [69,70]. Higher fibrosis grades were seen in patients with abnormal angiography according to a cross-sectional comparative investigation of 103 consecutive NAFLD patients by Nayebi et al, which revealed a significant difference in the level of hs-CRP according to elastography fibrosis grade [71].…”
Section: Cardiovascular Morbidity and Mortality And Nafldmentioning
confidence: 99%
“…Additionally, we are aware that these risk assessment models frequently do not take into consideration a number of the important CV disease risk factors, such as IR, obesity, and increased triglycerides. It has already been argued that the Framingham risk score understates the risk of CV disease in this population due to the similarities between metabolic syndrome and NAFLD [69,70]. As a result, it may not be appropriate to risk-stratify individuals with NAFLD solely based on the most recent CV risk score systems.…”
Section: Tools and Risk Scores For Assessing Cardiovascular Events In...mentioning
confidence: 99%
See 2 more Smart Citations